Monitoring complex detectors: the uSOP approach in the Belle II experiment. (1st August 2017) - Capua, F. Di; Aloisio, A.; Ameli, F.; Anastasio, A.; Branchini, P.; Giordano, R.; Izzo, V.; Tortone, G.
Abstract: uSOP is a general purpose single board computer designed for deep embedded applications in control and monitoring of detectors, sensors and complex laboratory equipments. It is based on the AM3358 (1 GHz ARM Cortex A8 processor), equipped with USB and Ethernet interfaces. On-board RAM and solid state storage allows hosting a full LINUX distribution. In this paper we discuss the main aspects of the hardware and software design and the expandable peripheral architecture built around field busses. We report on several applications of uSOP system in the Belle II experiment, presently under construction at KEK (Tsukuba, Japan). In particular we will report the deployment of uSOP in the monitoring system framework of the endcap electromagnetic calorimeter.